2003
DOI: 10.1111/j.1572-0241.2003.08674.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Early Surgery for Crohn's Disease: Implications for Early Treatment Strategies

Abstract: The rate of surgery is high in the first 3 yr after diagnosis of Crohn's disease, particularly in the first 6 months. These results suggest that improved risk stratification and potent therapies with rapid onset of action are needed to modify the natural history of Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(36 citation statements)
references
References 15 publications
1
32
0
3
Order By: Relevance
“…The literature, however, is limited as it deals chiefly with the impact of tobacco in patients with CD undergoing resection [14][15][16][17]. While previous research on patients with CD has emphasized the influence of tobacco exposure on the course of the disease [1,6,[8][9][10][11][18][19][20][21], there has been a limited focus on the effect that smoking may or may not have on the surgical outcome. The present work demonstrates that current smokers experienced increased 30-day postoperative complications (primarily related to infectious and pulmonary-related postoperative complications) and readmission compared with non-or ex-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The literature, however, is limited as it deals chiefly with the impact of tobacco in patients with CD undergoing resection [14][15][16][17]. While previous research on patients with CD has emphasized the influence of tobacco exposure on the course of the disease [1,6,[8][9][10][11][18][19][20][21], there has been a limited focus on the effect that smoking may or may not have on the surgical outcome. The present work demonstrates that current smokers experienced increased 30-day postoperative complications (primarily related to infectious and pulmonary-related postoperative complications) and readmission compared with non-or ex-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the operative rate is estimated to be 80% at 20 years after onset of the disease [1,2,3]. After surgery, 40% of patients are symptomatic within 4 years [4], and many patients (≈30%) experience disease recurrence and require a second operation within 10 years [5].…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative risk of surgery after diagnosis has been estimated to be around 80% [10,12,13,21,22] and the very recent observations from the population-based Olmsted County also confirm surgery rates found after 20 years of disease duration in our study [23]. When comparing the characteristics of the population of postoperative patients, we observed that mean age at first intestinal resection was nearly 10 years higher compared to other cohorts [24], which may indicate either that a significant effort has been made and achieved to delay the time to first RS, or that the disease remained undetected for a longer period before diagnosis [25], which might be the case for ileal diseases [26].…”
Section: Discussionmentioning
confidence: 99%